Pengaruh Penyuluhan Siaga Bencana terhadap Peningkatan Preparedness Bencana Gempa Bumi dan Tsunami Masyarakat Pesisir Pantai Negeri Rutah Kabupaten Maluku Tengah - A. Miftahul Khair; Rigoan Malawat; Usman Barus Ohorella (Jurnal Kesehatan Terpadu (Integrated Health Journal), 2021)
Indonesia, including the Maluku Islands, is included in an earthquake and tsunami-prone area because it is the meeting point of the Eurasian Plate and the Australian Plate. Improving preparedness aims to prepare people, so they don't panic too much when a disaster occurs to save themselves and their families from minimizing losses. Most of the people of Negeri Rutah work as fishermen and move around the coast, thus placing the community at high risk of earthquakes and tsunamis. This quantitative research uses a quasi-experimental method: pre-post test without a control group. The research sample is the coastal community of the State of Rutah, totaling 84 families. Counseling using disaster preparedness videos and earthquake and tsunami booklets. The results showed that didn't normally distribute the data with the Wilcoxon test results before and after intervention, p-value=0.001 (p<0.005), meaning that there was a significant effect of counseling on emergency response to the earthquake and tsunami on increasing preparedness of coastal communities in Negeri Rutah. The community and local government are expected to follow updates related to disaster preparedness, either seeking information through social media or participating in disaster-related socialization.